Pembayaran Zakat Fitrah dalam Tradisi Metraen Bhekal Bineh di Bangkalan Madura Perspektif ‘Urf - Galuh Widitya Qomaro; Nia Ningsih (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2022)
The metraen bhekal bineh tradition in Banyuajuh, Bangkalan, Madura requires prospective husbands to pay zakat fitrah for their prospective wives in the form of money or rice. This study aims to determine the practice of the metraen bhekal bineh tradition and to find out the review of Islamic law on the metraen bhekal bineh tradition in Banyuajuh, Bangkalan, Madura. This research is a field research with qualitative methods and a sociological juridical approach. Sources of data used are primary data and secondary data. Data collection techniques through observation, interviews, and documentation were analyzed using the inductive method. Based on the results of the study, it can be concluded that the metraen bhekal bineh tradition in Banyuajuh, Bangkalan Madura in terms of Islamic law is permissible because it is a tradition that grows and develops with good values ​​in society. The husband's obligation to pay zakat fitrah for his future wife is a customary obligation, not an obligation as required by Islamic law.